ANALISIS POLA PRODUKTIVITAS DAN FAKTOR PENENTU USAHA TANI KENTANG DI JAWA BARAT - Rasmikayati, Elly; Rachmawati, Erna; Saefudin, Bobby Rachmat (Jurnal Pertanian Agros, 2026)
Potato (Solanum tuberosum L.) is a strategic horticultural commodity in West Java, making micro-level empirical evidence essential to understand productivity variation at the farm level. This study aims to (1) describe the characteristics of potato farmers and potato farming in West Java; (2) describe land area, production, and potato productivity at the farmer level; and (3) analyze the effects of farmer and farm characteristics on potato productivity. The study employed a quantitative survey approach involving 210 potato farmers in West Java selected through simple random sampling. Data were analyzed using descriptive statistics and multiple linear regression (OLS). Descriptive results show an average landholding of 1.25 ha, production of 26.86 tons per cropping season, and productivity of 21.44 tons/ha; approximately 66.19% of farmers achieved productivity ≥20 tons/ha. Regression results show that age and seed use per hectare significantly and positively influence productivity, while experience and equity percentage significantly but negatively influence it. Other variables, including education, percentage of irrigated land, labor, fertilizer, pesticides, and other costs per hectare, have no significant impact. These findings highlight the importance of strengthening the management of key inputs (especially seed), improving access to productive financing, and providing technical extension support to enhance potato productivity at the farm level in West Java.